Analisis Pengelolaan Keuangan Sekolah di SMP Plus Baabussalam - Neka Zulwiddi; Hamdi Abdul Karim (Universitas 45 Surabaya, 2024)
School financial management is very much needed in educational institutions so that they are more qualified and the institutions are more quality. Therefore, in conducting excellent management of financial problems very much needed human resources that are professional in carrying out financial management in the institution of education.So the problems of financial management in educational institutions are managed effectively and effectively if a school financial management team is formed that is given to the human resources that are expert in the field. The purpose of this research is to understand the financial management system of schools in the most special educational institutions in the SMP Plus Babussalam can use the principles of transparency and accountability in the educational institution. This research uses qualitative research description and library in the SMP Plus Baabussalam. The head of the foundation as well as the entity of this educational institution and other stakeholders have interfered in various school neighborhoods. It is true that all implementation of financial statements is transparent and comply with the regulations that have been established by the government.